2022
DOI: 10.3390/md20030181
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan (Undaria pinnatifida)/Polydopamine Composite-Modified Surface Promotes Osteogenic Potential of Periodontal Ligament Stem Cells

Abstract: Fucoidan, a marine-sulfated polysaccharide derived from brown algae, has been recently spotlighted as a natural biomaterial for use in bone formation and regeneration. Current research explores the osteoinductive and osteoconductive properties of fucoidan-based composites for bone tissue engineering applications. The utility of fucoidan in a bone tissue regeneration environment necessitates a better understanding of how fucoidan regulates osteogenic processes at the molecular level. Therefore, this study desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…This is also supported by decrease in LAMP2 membrane expression, particularly after treatment with vLMW-F, which has been correlated with vesicles secretory activity of cells. Data in the literature confirm some links between fucoidan and actin pathway, such as decrease in expression of genes implicated in polymerization, organization and stabilization [ 57 ] or disruption of F-actin stress fibers [ 58 , 59 ]. In this context and as a first hypothesis, the difference between native and vLMW forms might be explained by variation in the internalized amount of the different species, especially for their molecular weight differences.…”
Section: Discussionmentioning
confidence: 89%
“…This is also supported by decrease in LAMP2 membrane expression, particularly after treatment with vLMW-F, which has been correlated with vesicles secretory activity of cells. Data in the literature confirm some links between fucoidan and actin pathway, such as decrease in expression of genes implicated in polymerization, organization and stabilization [ 57 ] or disruption of F-actin stress fibers [ 58 , 59 ]. In this context and as a first hypothesis, the difference between native and vLMW forms might be explained by variation in the internalized amount of the different species, especially for their molecular weight differences.…”
Section: Discussionmentioning
confidence: 89%
“…Another important signaling pathway influenced by PDLSC-CM involves the actin cytoskeleton, which generally influences diverse cellular functions, including communication with the ECM [ 50 , 51 ]. Our previous study suggested that actin cytoskeleton dynamics are among the key signaling pathways involved in enhancing the osteogenic potential of PDLSCs [ 24 ]. Several studies have also reported the significant impact of the mechanisms of the actin cytoskeleton in the osteogenic commitment of MSCs and osteogenic cells [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing was performed as described previously [ 24 ]. In brief, total RNA was extracted from PDLSCs cultured under different conditions, and the 500 ng of total RNA was prepared.…”
Section: Methodsmentioning
confidence: 99%
“… Hagar MN et al/2021 44 PDLSC Osteogenic differentiation Activation of the autophagy pathway by up-regulation of β-microtubulin III and down-regulation of chelator 1 / p62 thereby enhancing osteogenesis in PDLSCs slices Zhang Y et al/2021 45 PDLSC Neurogenic differentiation It can differentiate into neurogenic cells and recruit endogenous neural stem cells at the injury site. Mohebichamkhorami F et al/2022 46 PDLSC Osteogenic differentiation Receiving osteogenic induction by affecting the KEGG pathway Kwack KH et al/2022 47 SCAP Osteogenic differentiation Berberine (BBR) stimulates the Wnt/β-catenin pathway and induces osteogenic differentiation of SCAPs. Cui Y et al/2020 48 SCAP Neurogenic and vasculogenic differentiation Further evidence of the potential for neural differentiation and angiogenic differentiation of SCAPs through induction of biological potential Liu J et al/2022 49 DFSC Osteogenic differentiation Co-culture of HUVECs with DFSCs revealed that their secreted angiogenic factors stimulated osteogenic differentiation of DFSCs Bok JS et al /2018 50 …”
Section: Dental-derived Mesenchymal Stem Cellsmentioning
confidence: 99%